Type Synthesis of 3R2T Hybrid Robot Mechanisms based on Serial-opened-chain Unit - Chen Hai; Qin Youlei; Cao Yi (Jixie chuandong)
By analyzing the characteristics of structures for the lower- mobility serial robot mechanism and parallel robot mechanism,a systematic and effective type synthesis including the definition and symbol denotation method of both hybrid robot with a parallel mechanism and multi- parallel mechanisms method is proposed for hybrid robot mechanisms based on the principle of movement spiral linear independence and units of the lower- mobility serial mechanism with single- opened- chain limb. Firstly,type synthesis of 3T2 R 5- DOF serial mechanism with single- opened- chain is classified based on the screw theory,then the type synthesis of 3T2 R hybrid mechanisms are accomplished by regarding parallel mechanism as a complex kinematic unit and replacing an equal DOF kinematic chain limb in lower- mobility serial mechanism with single- opened- chain limb. Finally,other type synthesizes for other type synthesizes of 3T2 R hybrid mechanism are generated by the linear combination of the kinematics screw.